THE DEVELOPMENT OF THE STRATEGY COMPETENCE OF STUDENTS IN READING ESP TEXTS - Vitaliy Volik (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article deals with the problem of the development of strategic skills of ESP reading. There has been grounded the necessity of students' mastering the above mentioned competence. The terms "reading strategies" and "compression (sense reduction) strategies" have been defined. These strategies fall into the following groups: planning (framing), inferring, hypothesis testing (evaluating), revising hypotheses (correcting). The author gives a full description of the strategies. The strategic skills are suggested to be developed with the help of corresponding exercises and tasks. It has been proved that pre-reading exercises aim to form strategic skills of planning, reading exercises and tasks enable to use reading strategies of inferring and compression while post-reading tasks help to develop strategies of evaluating and correcting. The research results can be used for further studies of the problem.